How do students' beliefs about mathematics ability change in their first year at university? - Campbell, Anita (Critical Studies in Teaching and Learning, 2023)
The affective dimension of students’ transition into university is an area of development that has the potential to improve student success. Large-scale research suggests that developing a growth mindset belief –that academic ability can always be expanded–may be especially helpful  for  first  generation  students.  A  starting  point  for  developing  growth  mindsets  as  one type  of  affective  support  for  students  is  to  investigate how  we  can  position  students  on  the fixed-to-growth   spectrum   of   beliefs   about   academic   ability. This mixed-methods study considers the changes during their first year of university in the mindset beliefs held by two representative first-year mathematics students, one who passed and one who had to repeat the   second   semester   of   mathematics. Without experiencing interventions   aimed   at developing  growth  mindsets,  both  students  showed  small  shifts  towards stronger growth mindsets  over  their  first  year. Limitations  with  assessing  mindsets are  acknowledged and recommendations for future research in this area are suggested.